114 - PREVALENCE OF SOCIAL DETERMINANTS AMONG US RESIDENTS WITH HEART FAILURE BY RACE/ETHNICITY AND HOUSEHOLD INCOME - Lajjaben Patel, MBBS; Nidhish Lokesh, BS; Shreya Rao, MD MPH; Tiffany M. Powell-Wiley, MD MPH; Andrew Sumarsono, MD MPH (Elsevier, 2023)
Therapeutic Area: Heart Failure Background: Social determinants of health (SDOH) are associated with heart failure (HF) outcomes. However, there are no data on national prevalence of SDOH among ambulatory HF patients. We aimed to address this knowledge gap by investigating the national prevalence of SDOH among ambulatory HF patients across racial, ethnic, and income groups. Methods: We collected data from the 1999-2018 National Health and Nutrition Examination Survey (NHANES). Patients with self-reported HF were included. We extracted data pertaining to domains of SDOH including socioeconomic position, access to care, environment, and health status. We used appropriate survey weighing methods in our analyses. Results: 1906 individuals were included, representing 5.25 million people in the US (Mean population age 66.3 years, 48.3% female, 71.8% White, 14.7% Black, 8.2% Hispanic, and 5.3% Asian/other). 33.7% population had a self-reported income <130% federal poverty limit (FPL), while 45.4% had incomes between 130-350% FPL and 20.9% had incomes >350% FPL.When individual SDOH factors were aggregated into specific SDOH domains, 81.4% of HF patients reported being affected by at least 2 SDOH domains, with a mean of 2.1 reported domains per patient. HF patients with incomes <130% FPL were impacted with a mean of 2.5 SDOH domains, compared to 2.0 and 1.6 domains for patients with incomes between 130-350% FPL and 350+% FPL, respectively.White patients with HF reported a lower mean number of 2.0 SDOH domains than Black (2.3 SDOH domains), Hispanic (2.4 SDOH domains), and Asian/Other (2.2 SDOH domains).Race/ethnic differences were noted in education, uninsurance rates, food insecurity, household crowding, and sleep deprivation (P<0.0001 for all) (Figure 1A).Differences in unemployment, high school education, uninsurance rates, household crowding, sleep deprivation, physical inactivity, and disability were observed across income thresholds (P<0.01 for all) (Figure 1B). Conclusions: In conclusion, we observe considerable SDOH burden in HF patients that is unequally distributed among income and racial/ethnic groups. Future research to determine clinically impactful SDOHs, and social interventions directed at modifying them can potentially improve HF outcomes.